Psychological Ownership in Organizations: The Role of Person-Organization Fit and Consequences on Support for Change and Organizational Citizenship Behavior - Alhadar, Fadhliah M; Hidayanti, Ida (Society, 2021)
This study examines the antecedent and consequences of psychological ownership, where employees develop possessive feelings towards the organization. Person-Organization Fit (PO-Fit) is required to increase psychological ownership through various organizational activities. Psychological ownership produces significant psychological, emotional, and behavioral consequences, including employees support for change and Organizational Citizenship Behavior (OCB). This study involved 210 staff from educational institutions. A total of 191 survey questionnaires were returned, and 121 were eligible. According to hierarchical regression analysis, the result indicated that PO-Fit had a positive effect on psychological ownership (?=0.42, t=4.81), psychological ownership had a positive effect on support for change (?=0.26, t=4.01) and OCB (?=0.21, t=3.12). The study concluded that psychological ownership is necessary to support positive organizational behavior.